The Law of One Price - A Case Study - Jonathan Haskel; Holger C. Wolf (Center for Economic Studies and ifo Institute (CESifo), 2001)
We use retail transaction prices for a multinational retailer to examine the extent and permanence of violations of the law of one price (LOOP). For identical products, we find typical deviations of twenty to fifty percent, though there is muted evidence for convergence over time. Such differences might be due to differences in local costs. If so, relative prices of similar products (round versus square mirrors) should be equal across countries. In fact, relative prices vary significantly across very similar goods within a product group; indeed, the ordering of common currency prices often differs for similar products. The finding suggests that differences in local distribution costs, local taxes, and probably tariffs do not explain the price pattern, leaving strategic pricing or other factors resulting in varying markups as alternative explanations for the observed divergences.
Keywords: 330; Law of one price; arbitrage; exchange rate passthrough; price setting